Kajian Pembangunan M-Learning Aplikasi TOS Bagi Kursus DCC40163 ( Theory Of Structure) - Aniza Tahir,; Mohmad Nazri Mahbob,; Shahrizal Samsudin, (Multidisciplinary Applied Research and Innovation, 2023)
Mobile learning (m-learning) is a method of teaching and learning during the covid-19 pandemic hit the world. Mobile learning (m-learning) can be defined as any form of teaching and learning when users interact through mobile devices such as PDAs, palmtops, iPhones, handheld computers, smartphones or other gadgets. This study aims to evaluate the usability of the mobile application 'TOS Apps' developed for DCC40163 course, Theory of Structure, Civil Engineering Diploma, Sultan Azlan Shah Polytechnic. This mobile application is developed using Glide and Canva applications based on five (5) stages, which are analysis stage, design stage, development stage, implementation stage and evaluation stage.  The study was conducted through questionnaire that involves fourth semester diploma students in Civil Engineering who take DCC40163 course. The respondent consisted of 26 students in session 1 2021/2022, 23 students in session 2 2021/2022 and 38 students in session 1 2022/2023 The data collected was analysed using the Statistical Packages for Social Science (SPSS) Version 12.0. The results of the study shows that students were very satisfied with this developed application. Besides that, Min value for the aspects of user-friendly was also very high. In can be concluded that the construction ofaplikasi TOS was successfully developed and potentially implemented in teaching and learning of the DCC40163 course, Theory Of Structure.